2013
DOI: 10.1002/jor.22462
|View full text |Cite
|
Sign up to set email alerts
|

Median nerve deformation and displacement in the carpal tunnel during finger motion

Abstract: The objective of this study was to evaluate the correlations between deformation and displacement of median nerve and flexor tendons during finger motion in the carpal tunnel for both carpal tunnel syndrome (CTS) patients and healthy controls. Sixtytwo wrists of 31 asymptomatic volunteers and fifty-one wrists of 28 idiopathic CTS patients were evaluated by ultrasound. The displacement of the median nerve and the middle finger flexor digitorum superficialis (FDS) tendon, as well as area, perimeter, aspect ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
64
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(65 citation statements)
references
References 12 publications
1
64
0
Order By: Relevance
“…Recently, several studies reported that the median nerve moves longitudinally and transversely in response to active tendon motion in the carpal tunnel during finger or wrist movement (Nakamichi and Tachibana 1992;Erel et al 2003;Yoshii et al 2009;van Doesburg et al 2010). Additionally, some authors have used transverse ultrasound to evaluate median nerve motion in the carpal tunnel (Yoshii et al 2009(Yoshii et al , 2013van Doesburg et al 2010van Doesburg et al , 2012Wang et al 2014a, b;Nanno et al 2015). With use of this modality, it has previously been determined that the median nerve becomes displaced palmarly and gets compressed against the TCL in active finger flexion in healthy subjects and in patients with CTS (Yoshii et al 2009(Yoshii et al , 2013van Doesburg et al 2012;Wang et al 2014a, b).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, several studies reported that the median nerve moves longitudinally and transversely in response to active tendon motion in the carpal tunnel during finger or wrist movement (Nakamichi and Tachibana 1992;Erel et al 2003;Yoshii et al 2009;van Doesburg et al 2010). Additionally, some authors have used transverse ultrasound to evaluate median nerve motion in the carpal tunnel (Yoshii et al 2009(Yoshii et al , 2013van Doesburg et al 2010van Doesburg et al , 2012Wang et al 2014a, b;Nanno et al 2015). With use of this modality, it has previously been determined that the median nerve becomes displaced palmarly and gets compressed against the TCL in active finger flexion in healthy subjects and in patients with CTS (Yoshii et al 2009(Yoshii et al , 2013van Doesburg et al 2012;Wang et al 2014a, b).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, some authors have used transverse ultrasound to evaluate median nerve motion in the carpal tunnel (Yoshii et al 2009(Yoshii et al , 2013van Doesburg et al 2010van Doesburg et al , 2012Wang et al 2014a, b;Nanno et al 2015). With use of this modality, it has previously been determined that the median nerve becomes displaced palmarly and gets compressed against the TCL in active finger flexion in healthy subjects and in patients with CTS (Yoshii et al 2009(Yoshii et al , 2013van Doesburg et al 2012;Wang et al 2014a, b).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations